Pemanfaatan Limbah Serbuk Kayu Sebagai Penguat Pada Matriks Getah Pinus-Epoxy Dan Dengan Dan Tanpa Perlakukan NaOH - kencanawati, putri kusuma; Suardana, NPG; Sugita, I Ketut Gede (Jurnal Energi Dan Manufaktur; Vol 16 No 1 (2023)DO - 10.24843/JEM.2023.v16.i01.p02, 2023)
The use of wood as the main material for making furniture is one of the causes of the increasing amount of sawdust waste. Efforts that can be made to reduce the amount of wood waste is to use it as a raw material for the manufacture of particleboard/composite material. The manufacture of particleboard is currently still using synthetic materials that are difficult to degrade by nature (non-biodegradable). Therefore, in this study using materials that can be naturally degraded (biodegradable), namely using sawdust waste which is treated with immersion with variations of NaOH (5%, 7.5% and 10%) for 1 hour first to remove dirt on the soil. powder, then mixed with pine resin/epoxy matrix with a composition of wood powder (10%, 15%, and 20%). Furthermore, physical tests will be carried out, namely density and water absorption as well as bending tests in accordance with ASTM D790-03. Manufacture of composite wood powder/pine sap/epoxy hand lay up method in the process. The results of the bending test showed that the highest bending stress was in the composition of sawdust: matrix (15:85) immersed in 5% NaOH, which was 79.22 MPa. The highest strain value in the composition of sawdust: matrix (20:80) without NaOH immersion was 0.088 and the highest modulus of elasticity was in the composition 15:85 with 5% NaOH immersion which was 744 MPa. Density test showed that the highest density value was found in the composition of 20;80 5% NaOH immersion with a density value of 1.088 gr/cm3, the smallest density value was in the composition of 10;90 10% NaOH immersion of 1.021 gr/cm3. In the water absorption test, the highest value was shown in the composition of 20:80 immersion in 10% NaOH with a value of 17.59% and the lowest value was shown in the composition of 10:90 without immersion in NaOH with a value of 6.81%. The results of this study indicate that the increase in the value of stress, strain and modulus of elasticity from the bending test is influenced by the concentration of alkaline solution, where the more concentrated the NaOH content, the bending strength and density will decrease but inversely proportional to water absorption.